2009
DOI: 10.1016/j.cortex.2008.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Deficient mental own-body imagery in a neurological patient with out-of-body experiences due to cannabis use

Abstract: Mental imagery Body Drug use a b s t r a c tIn the present work, we report repeated out-of-body experiences (OBEs) in a patient with tetraplegia and severe somatosensory loss due to multiple sclerosis and predominant involvement of the cervical spinal cord. OBEs were experienced on a daily basis and induced by cannabis treatment that was started for severe spasticity with painful cramps and cloni.In order to investigate the link between OBEs and mental own-body imagery, the patient was asked to imagine himself… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…Although rates of out-of-body experiences were lower in our polydrug sample, they were still higher than those found in normative groups (e.g., Braithwaite et al, 2010;Easton et al, 2009). In this regard, we note that cannabis use has also been linked to out-of-body phenomena (e.g., Overney et al, 2009;Wilkins et al, 2011); moreover, 99% of the current sample reported lifetime use of cannabis, most of whom reported very frequent use (see Wilkins et al, 2011, for more a more complete breakdown of drug use in the overall sample). Future exploration of interactions among the various neurochemical systems affected by these drugs, differential effects of acute and chronic exposure, and their relations to gross neuroanatomical features, on susceptibility to anomalous and psychotic experiences is also warranted (Corlett, Frith, & Fletcher, 2009).…”
Section: Wilkins Girard Cheynecontrasting
confidence: 56%
See 1 more Smart Citation
“…Although rates of out-of-body experiences were lower in our polydrug sample, they were still higher than those found in normative groups (e.g., Braithwaite et al, 2010;Easton et al, 2009). In this regard, we note that cannabis use has also been linked to out-of-body phenomena (e.g., Overney et al, 2009;Wilkins et al, 2011); moreover, 99% of the current sample reported lifetime use of cannabis, most of whom reported very frequent use (see Wilkins et al, 2011, for more a more complete breakdown of drug use in the overall sample). Future exploration of interactions among the various neurochemical systems affected by these drugs, differential effects of acute and chronic exposure, and their relations to gross neuroanatomical features, on susceptibility to anomalous and psychotic experiences is also warranted (Corlett, Frith, & Fletcher, 2009).…”
Section: Wilkins Girard Cheynecontrasting
confidence: 56%
“…However, different aetiologies may lead to similar disintegration of vestibular and sensorimotor processes (e.g., Overney, Arzy, & Blanke, 2009). Recent behavioural data also supports proposals of temporal-lobe instability and abnormal frontal-parietal connectivity (Easton, Blanke, & Mohr, 2009) in relation to out-of-body experiences.…”
Section: Wilkins Girard Cheynementioning
confidence: 55%
“…We have reviewed behavioural and neuroimaging studies suggesting that the brain processes involved in the deliberate mental transformation of one's own body may be the same as those implicated in perspective taking (for review see Kessler & Wang, 2012;Kessler & Thomson, 2010;Kessler & Rutherford, 2010;van Elk & Blanke, 2013;Popescu & Wexler, 2012) and it was suggested that this provides a logical link to OBE. This is echoed by the relevant literature on OBE (Arzy et al, 2006;Blackmore, 1982;Olaf Blanke & Arzy, 2005;Brugger, 2002;Cook & Irwin, 1983;Easton et al, 2009;Mohr, Blanke, & Brugger, 2006;Overney, Arzy, & Blanke, 2009), yet, only a handful of these studies actually explored performance on a perspective taking task in direct relation to samples reporting OBEs -and these have produced mixed results Easton et al, 2009).…”
Section: Revisiting Mixed Findings On the Link Between Obe And Vptmentioning
confidence: 99%
“…In addition, behavioral studies have argued that the brain processes involved in the mental transformation of one’s own body may be the same as those implicated in the computation of an exocentric perspective (for review, see Kessler and Rutherford, 2010; Kessler and Thomson, 2010; Kessler and Wang, 2012; Popescu and Wexler, 2012; van Elk and Blanke, 2013) and particularly in the OBE (Cook and Irwin, 1983; Blackmore, 1987; Brugger, 2002; Blanke and Arzy, 2005; Blanke et al, 2005; Arzy et al, 2006; Mohr et al, 2006; Easton et al, 2009; Overney et al, 2009; Braithwaite et al, 2011). Most of the latter studies used performance at the “own-body-transformation” (OBT) task to explore perspective-taking and have implicated the temporal–parietal junction in the mental transformation of one’s own body and perspective (see Blanke et al, 2005).…”
Section: Introductionmentioning
confidence: 99%